Chemical synthetic biology: a mini-review - Chiarabelli, Cristiano; Stano, Pasquale; Luisi, Pier Luigi (Frontiers in Microbiology, 2013)
Chemical synthetic biology (CSB) is a branch of synthetic biology (SB) oriented towards the synthesis of chemical structures alternative to those present in nature. Whereas SB combines biology and engineering with the aim of synthesizing biological structures or life forms that do not exist in nature – often based on genome manipulation, CSB uses and assembles biological parts, synthetic or not, to create new and alternative structures. A short epistemological note will introduce the theoretical concepts related to these fields, whereas the text will be largely devoted to introduce and comment two main projects of CSB, carried out in our laboratory in the recent years. The “Never Born Biopolymers” (NBB) project deals with the construction and the screening of RNA and peptide sequences that are not present in nature, whereas the “Minimal Cell” project focuses on the construction of semi-synthetic compartments (usually liposomes) containing the minimal and sufficient number of components to perform the basic function of a biological cell. These two topics are extremely important for both the general understanding of biology in terms of function, organization and development, and for applied biotechnology.